Multiple product plant utilizing the native produce of the T'boli and B'laan communities a plant design - Leonardo, Ma. Caterina A.; Madlambayan, Kathy E.; Peralta, Stephanie Joy L.
The spoilage of the crops of the neighboring TBoli and Blaan communities is the main issue to be addressed in this study. This study proposes to design an industrial plant that will make use of the surplus crops of the indigenous communities and turn them into higher-value products. In line with this, more people will benefit from the sales of the products and from the created job opportunities within the plant.The proposed products in the study are potato flour, kimchi and pickled pechay. Again, the raw material supply will come from the nearby TBoli and Blaan communities. Flour, which is usually used as a thickening agent and a primary ingredient in baked goods, is increasing in demand annually that importation is sometimes needed to satisfy this growing demand. Therefore, the use of cheaper alternative flour is encouraged instead of wheat flour to lessen its expensive importation. On the other hand, the sales of pickled products here in Asia have been constantly increasing, and the Philippines contributed about 0.05 percent of this increase in 2012. In the country, the most common and famous pickled product is the atchara or the pickled green papaya. Pickled pechay and kimchi would offer variety from the usual pickled products sold here in the country, and would hopefully increase the market demand for pickled products.In the process selection, several methods or techniques, such as pre-treatment and post blanching techniques, different drying methods, salting methods and fermentation temperature, were assessed. In determining the best methods, the most important factors that were considered are product quantity and quality, process efficiency and costs. The methods or techniques which increase the product quantity, enhance the product quality, increase the process efficiency and decrease the costs are that are more attractive to be implemented.The proposed plant will be located in General Santos City. This location is not only very accessible from the raw material supply, but is also accessible from the neighboring provinces which is advantageous in terms of marketing the products and distributing it to outside the vicinity. The plant is also proposed to reside near a residential area, therefore water, electricity and labor supply will not be a problem. Other consideration were also evaluated such as the sites proneness to geo-hazards, typhoons, floods and others natural disasters.